A Survey on Motivation for Choosing Science Subjects by Students of S.B. Women’s Higher Secondary School, Cuttack, Odisha - Pati, Jyotirmoyee (Stallion Journal for Multidisciplinary Associated Research Studies, 2023)
For the growth of technology and innovation, science education is essential. There remains a gender disparity in science education in India, though, as fewer females choose to major in science in upper secondary school. With an emphasis on the Indian context, this paper examines the body of research on the variables influencing students' decisions to study science. After that, a study programme is suggested to investigate these aspects in more detail, taking into account societal effects, professional objectives, intrinsic interest, and teacher impact. In the current study, the primary factor influencing the choice of scientific course was career possibility, which was followed by instructor and personal impact. Comprehending these incentives is essential for formulating tactics to encourage science education among Indian females.